2017
DOI: 10.1523/jneurosci.1797-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Neuroglial Metabolic Coupling after Peripheral Surgery

Abstract: Immune-related events in the periphery can remotely affect brain function, contributing to neurodegenerative processes and cognitive decline. In mice, peripheral surgery induces a systemic inflammatory response associated with changes in hippocampal synaptic plasticity and transient cognitive decline, however, the underlying mechanisms remain unknown. Here we investigated the effect of peripheral surgery on neuronal-glial function within hippocampal neuronal circuits of relevance to cognitive processing in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 69 publications
8
40
0
Order By: Relevance
“…In the present study, we showed that IL-1β and IL-6 levels were significantly increased and lasted for 8 days postsurgery. Our results were consistent with the previous studies [15,22,34], suggesting that the hippocampus is susceptible to neuroinflammation induced by anesthesia and surgery. However, the mechanism by which neuroinflammation leading to cognitive impairments following anesthesia and surgery remains unclear.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we showed that IL-1β and IL-6 levels were significantly increased and lasted for 8 days postsurgery. Our results were consistent with the previous studies [15,22,34], suggesting that the hippocampus is susceptible to neuroinflammation induced by anesthesia and surgery. However, the mechanism by which neuroinflammation leading to cognitive impairments following anesthesia and surgery remains unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Conditioned plasma was obtained from the blood sampled from anaesthetized rats subjected to tibia surgery (one rat per time point), a procedure adapted from an analogous surgery model on mice (Femenia et al., 2018; Terrando et al., 2013). Blood samples were taken before surgery (control), 1, 3, 6 and 24 h after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative cognitive dysfunction (POCD) is a chronic decline in cognitive function also associated with anesthesia/surgery. It was found that POCD was associated with astrocytic decreased Ca 2+ signaling along with enhanced synaptic transmission in the mouse hippocampus (35). The causal relationship between astrocyte and neuron dysfunctions in POCD remains to be established.…”
Section: Discussionmentioning
confidence: 99%